Global History and New Polycentric Approaches Europe, Asia and the Americas in a World Network System (Palgrave Studies in Comparative Global History, 2018)
This book is open access under a CC BY 4.0 license. Rethinking the ways global history is envisioned and conceptualized in diverse countries such as China, Japan, Mexico or Spain, this collections considers how global issues are connected with our local and national communities. It examines how the discipline had evolved in various historiographies, from Anglo Saxon to southern European, and its emergence in Asia with the rapid development of the Chinese economy motivation to legitimate the current uniqueness of the history and economy of the nation. It contributes to the revitalization of the field of global history in Chinese historiography, which have been dominated by national narratives and promotes a debate to open new venues in which important features such as scholarly mobility, diversity and internationalization are firmly rooted, putting aside national specificities. Dealing with new approaches on the use of empirical data by framing the proper questions and hypotheses and connecting western and eastern sources, this text opens a new forum of discussion on how global history has penetrated in western and eastern historiographies, moving the pivotal axis of analysis from national perspectives to open new venues of global history.